2017
DOI: 10.1007/s13748-017-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing multi-objective metaheuristics for solving a three-objective formulation of multiple sequence alignment

Abstract: Multiple sequence alignment (MSA) is an optimization problem consisting in finding the best alignment of more than two biological sequences according to a number of scores or objectives. In this paper, we consider a threeobjective formulation of MSA, which includes the STRIKE score, the percentage of aligned columns, and the percentage of non-gap symbols. The two last objectives introduce many plateaus in the search space, thus increasing the complexity of the problem. By taking as benchmark the BAliBASE data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…A Pareto-set can be found with multi-objective meta-heuristics, such as MOPSO [22] and NSGA-II [20]. We employ NSGA-II meta-heuristic, due to the better performance in comparison with other metaheuristics [23]. The input of the algorithm is (1) the set of sensors S, (2) the network links available between each node L, (3) the set of cloud nodes C c , (4) the map M(m, n) of the area and (5) the set of admissible coordinates for edge nodes L e .…”
Section: Stage-1: Transmission Time and Energymentioning
confidence: 99%
“…A Pareto-set can be found with multi-objective meta-heuristics, such as MOPSO [22] and NSGA-II [20]. We employ NSGA-II meta-heuristic, due to the better performance in comparison with other metaheuristics [23]. The input of the algorithm is (1) the set of sensors S, (2) the network links available between each node L, (3) the set of cloud nodes C c , (4) the map M(m, n) of the area and (5) the set of admissible coordinates for edge nodes L e .…”
Section: Stage-1: Transmission Time and Energymentioning
confidence: 99%
“…They belong to the class of evolutionary algorithms. Several studies ( [27,21,42]) demonstrated the strength of NSGA-II for solving MSA. NSGA-II works best when the number of objectives is upto three while NSGA-III is specially designed for handling more than three objectives.…”
Section: Multi-objective Metaheuristicsmentioning
confidence: 99%
“…During the last decade, we find several studies [20,21,22,23,24,25,26,27] with multiobjective formulation for MSA have been published -proposing two to four objective functions to capture and quantify different aspects of an alignment. Among them probably the most popular is the sum-of-pairs score and its weighted variants, where pairwise score is calculated for each pair of aligned sequences using a substitution matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinspired algorithms, such as Genetic Algorithms (GA), Simulated Annealing (SA), Particle Swarm Optimization (PSO), and Artificial Bee Colony Optimization (ABC), have been widely used in Multiple Sequence Alignment (MSA) research due to their remarkable ability to unearth optimal or near-optimal solutions [7,8]. These algorithms mimic natural processes or use population-based strategies, which help them find optimal solutions and avoid becoming stuck in local optima.…”
Section: Introductionmentioning
confidence: 99%